PENGARUH SENAM ERGONOMIK TERHADAP RENTANG GERAK PENDERITA OSTEOARTRITIS PADA LANJUT USIA - Andi Surya; Erna Rochmawati (Jurnal Keperawatan Terapan, 2021)
Osteoarthritis that occurs in the elderly is a chronic degenerative disease. This type of research uses quantitative with quasi-experimental, the type of pre-posttest design with control group design. The number of samples consisted of 16 elderly in the intervention group given ergonomic exercise and 16 in the control group. The intervention group was given ergonomic exercise, the control group was given elderly exercise. The results showed that there were significant differences in the two groups. Changes in range of motion also occurred changes between the range of motion of knee flexion, knee extension, plantar flexion of the ankle and dorsal flexion of the ankle, all significant with p less than 0.05. The conclusion of this study is that ergonomic exercise affects the range of motion of patients with osteoarthritis in the elderly.